Pengaruh Perputaran Modal Kerja Terhadap Profitabilitas Pada Perusahaan Manufaktur LQ-45 Periode 2015-2017 - Suci Rizky Amelia; Lukman Cahyono (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2020)
The purpose of this study was to analyze variables of working capital consists of cash turnover, receivables turnover, and inventory turnover on the Profitability. Profitability is measured by the proxy of return on assets. The study population used observational data in the manufacturing sector with the LQ-45 index listed on the Indonesia Stock Exchange in the 2015-2017 period of 10 companies. The research method uses an analysis multiple linear regression, classic assumptions test which include the normality, multicollinearity, heteroscedasticity and Autocorrelation tests, with hypothesis tests. The results showed that working capital variables (cash turnover, receivables turnover, and inventory turnover) has simultaneous influence to the Profitability. Working capital, namely is only cash turnover has a significant influence to the profitabilit meanwhile receivables turnover and inventory turnover have no influence to the profitability.